Selection Of Artemisia Annua L. Cell Lines For Production Of Cell Biomass, Artemisinin And Dihydroartemisinin - Ch’ng, Song Jin (2014)
Artemisia annua, an aromatic herbaceous plant, was found to produce artemisinin that had proven to have antimalarial properties. Callus culture of A. annua was successfully established from the leaf explants of in vitro plantlets by culturing onto MS basal medium supplemented with 0.5 mg/L BAP, 0.5 mg/L NAA and 0.5 g/L casein hydrolysate. Callus biomass induced from dTC2 clone (0.968 ± 0.067 g) was significantly higher than dTC1 clone (0.401 ± 0.098 g) after five weeks of culture. The callus induced from dTC1 clone was white, soft and sticky while callus derived from dTC2 clone was green and friable. Selection process was carried out from the callus derived from TC1, TC2, Highland, dTC1 and dTC2 clones of A. annua of Vietnam origin. A total of 67 callus cell lines were produced from the five clones of which 15 lines were derived from TC1, 10 from TC2, 20 from Highland, 12 from dTC1 and 10 from dTC2. However, only nine lines were selected from TC1, six lines from TC2, eight lines from dTC1, seven lines from dTC2 and four lines from Highland based on the growth stability throughout 13 subculture cycles. The selected callus cell lines were categorised into fast growing with growth index (GI) > 20, intermediate (15≤ GI ≤20) and slow (GI < 15) growing group. There were no slow growing callus cell lines derived from TC2 and dTC2 clones as the two clones had high biomass productivity in nature. Morphological characteristic of the callus were found to influence the growth of the callus cell lines of A. annua. Callus cell lines with low colour intensity produced higher cell biomass.